(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The study explores the effectiveness of case-based learning (CBL) as a pedagogical approach in enhancing the learning outcomes of secondary vocational students. CBL is a student-centered teaching strategy that encourages critical thinking, problem-solving, and the application of theoretical knowledge to real-world scenarios. This research looks at how CBL facilitates deeper engagement with the material it is used for, improves practical skills, and increases students’ retention of subject knowledge in the vocational sphere. The approach used was mixed methods methods integrating qualitative and quantitative data through surveys, interviews and classroom observations. The results indicate that case-based learning led to some significant improvements of students’ analytical and decision-making capabilities and students’ ability to use theoretical knowledge in practical situations. In addition, CBL motivated collaboration, and participation, creating a learning atmosphere that resembled work settings from the real world. The study suggests that case-based learning enables students to not only achieve academically, but also secure them necessary skills to help solve problems and think critically to face challenges of their future careers. This study shows that CBL is a good teaching method used in vocational education, and that it has the capacity to strengthen the whole educational experience of secondary vocational students.